Soya isoflavone consumption in relation to carotid intima–media thickness in Chinese equol excretors aged 40–65 years - Cai, Yun; Guo, Kaiping; Chen, Chaogang; Wang, Ping; Zhang, Bo; Zhou, Quan; Mei, Fang; Su, Yixiang (British journal of nutrition, 2012)
Previous studies have suggested that the daidzein metabolite equol rather than daidzein itself contributes to the beneficial effect of soya foods in the prevention of CVD. The aim of the present study is to examine the proportion of equol excretion in Chinese adults and compare plasma lipids and carotid artery intima–media thickness (IMT) between equol excretors and non-excretors, and to evaluate the effect of soya isoflavone intakes on serum lipids and IMT in either equol excretors or non-excretors. Subjects (n 572; women n 362, men n 210) were recruited for the present study. An overnight urine sample was provided by each subject on their usual diet to quantify urinary concentrations of daidzein and equol. Far-wall IMT was determined by B-mode ultrasound in the right carotid at two sites, carotid bulb (CB-IMT) and common carotid artery (CCA-IMT), and fasting serum lipids were measured. Habitual dietary intakes were estimated with a FFQ, and soya isoflavone intake derived from the FFQ was assessed. Of the 572 subjects, the proportion of equol excretors on their usual diet was 25·0 % (n 143). Compared with non-excretors, equol excretors showed significantly lower serum TAG ( − 38·2 (95 % CI − 70·4, − 5·9) %, P = 0·012) and CCA-IMT ( − 4·9 (95 % CI − 9·7, − 0·3) %, P = 0·033). Equol excretors with higher daily isoflavone intakes ( − 5·4 mg/d) had significantly lower IMT ( − 16·2 %, P = 0·035) and tended to have higher HDL-cholesterol (P = 0·055) than did those with lower daily isoflavone intakes (1·5 mg/d), while no association was observed between soya isoflavone intakes and serum lipids or IMT in non-excretors. In conclusion, the benefits of soya isoflavones in preventing CVD may be apparent among equol excretors only.